Assessing the appropriateness and adequacy of the provision for housing under the haddul-kifayah for asnaf faqr and asnaf miskin - Hasan, Sharina Farihah; Abdul Rashid, Khairuddin; Ahmad Sarkawi, Azila (Procurement and Project Delivery System Research Unit, IIUM, 2017)
Haddul kifayah can be referred to as a tool applied by administrators of zakat in determining if a particular household is considered as either asnaf faqr or asnaf miskin and subsequently in determining the amount of zakat assistance to be provided to the household. There are various components that form the haddul kifayah among them is the provision of shelter or housing for the household. Zakat administrators employ their own standards in determining the appropriateness and adequacy of the components. This paper reports on a study that focuses on the shelter or housing component of the haddul kifayah. The objectives of the study are to (i) identify the subcomponents forming the shelter or housing component of the haddul-kifayah and their corresponding monetary allocations as applied by selected zakat administrator in Malaysia; (ii) assess whether the identified sub-components and their corresponding monetary allocation are appropriate and adequate in meeting the current shelter or housing needs of the asnaf faqr or asnaf miskin respectively. The study involved reviewing related literature and the carrying out of a convenient sample survey among households that reside in houses deemed appropriate for the provision of shelter or housing for asnaf faqr or asnaf miskin. The objective of the survey is to determine the appropriateness of the houses, utilities and facilities thereto and the associated monthly costs. The outcome from the survey was then contrasted with the outcome from the literature review. Key findings from the study suggest that the sub-components and their corresponding monetary allocation forming the shelter or housing component of the haddul kifayah as currently being applied by the selected zakat administrators are neither appropriate nor adequate in meeting the current needs of the asnaf faqr or asnaf miskin respectively. The paper concludes with a recommendation that zakat administrators should consider revising the standards used in determining the appropriateness and adequacy of the subcomponents forming the shelter or housing component of the haddul-kifayah. To this end a list of the sub-components and their corresponding monetary allocations that are deemed to be more reflective of the current needs of the asnaf faqr or asnaf miskin respectively are provided for consideration by zakat authorities in Malaysia.